PENGEMBANGAN MODUL BERBASIS POE (PREDICT-OBSERVE-EXPLAIN) PADA MATERI POKOK KOLOID UNTUK KELAS XI SMA/MA DALAM MENUNJANG PROSES PEMBELAJARAN - Rahmadini, Martalia; Erviyenni, Erviyenni; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to develop a module based on POE (Predict-Observe-Explain) on colloid subject matter for the eleventh grade of Senior High School which is valid according to the aspects of substance, language, presentation and graphic in supporting the learning process. The type of the research that be used is Research and Development with developing process referring to the 4D development methodology including Define, Design, Develop and Disseminate. This research was only be done till the development level. Research object is colloid module based on POE. Data accumulation is in the form of validation sheet that was given to three validators and response-used sheet to test the module practically that was given to three chemical teachers and 15 eleventh grade learners in science class of senior high school. The validation score is averaged to 4 aspects of module appropriateness including the appropriate aspects of substance, language, presentation and graphic that is consecutively about 95,45%, 93,33%, 96,67%, and 95,83%. The overall average score in validation of POE-based colloid module is 95,32% with very valid criteria. According to the data analysis can be concluded that the developed POE-based module on colloid subject matter is stated as valid to be used in supporting the learning process.Key Words: Module, POE (Predict-Observe-Explain), Colloid